Implementation of selective prevention for cardiometabolic diseases; are Dutch general practices adequately prepared?. (2nd January 2018) - Stol, Daphne M.; Hollander, Monika; Nielen, Markus M. J.; Badenbroek, Ilse F.; Schellevis, François G.; de Wit, Niek J.
Abstract: Objective: Current guidelines acknowledge the need for cardiometabolic disease (CMD) prevention and recommend five-yearly screening of a targeted population. In recent years programs for selective CMD-prevention have been developed, but implementation is challenging. The question arises if general practices are adequately prepared. Therefore, the aim of this study is to assess the organizational preparedness of Dutch general practices and the facilitators and barriers for performing CMD-prevention in practices currently implementing selective CMD-prevention. Design: Observational study. Setting: Dutch primary care. Subjects: General practices. Main outcome measures: Organizational characteristics. Results: General practices implementing selective CMD-prevention are more often organized as a group practice (49% vs. 19%, p  = .000) and are better organized regarding chronic disease management compared to reference practices. They are motivated for performing CMD-prevention and can be considered as 'frontrunners' of Dutch general practices with respect to their practice organization. The most important reported barriers are a limited availability of staff (59%) and inadequate funding (41%). Conclusions: The organizational infrastructure of Dutch general practices is considered adequate for performing most steps of selective CMD-prevention. Implementation of prevention programs including easily accessible lifestyle interventions needs attention. All stakeholders involved share the responsibility to realize structural funding for programmed CMD-prevention. Aforementioned conditions should be taken into account with respect to future implementation of selective CMD-prevention. Key Points:   There is need for adequate CMD prevention. Little is known about the organization of selective CMD prevention in general practices.    The organizational infrastructure of Dutch general practices is adequate for performing most steps of selective CMD prevention.    Implementation of selective CMD prevention programs including easily accessible services for lifestyle support should be the focus of attention.    Policy makers, health insurance companies and healthcare professionals share the responsibility to realize structural funding for selective CMD prevention.